2014
DOI: 10.1037/a0034550
|View full text |Cite
|
Sign up to set email alerts
|

Impact of male partner responses on sexual function in women with vulvodynia and their partners: A dyadic daily experience study.

Abstract: Objective. There is a paucity of research investigating the role of interpersonal variables in vulvodynia -a prevalent, chronic, vulvo-vaginal

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4
1

Relationship

4
5

Authors

Journals

citations
Cited by 86 publications
(46 citation statements)
references
References 45 publications
5
40
0
1
Order By: Relevance
“…In turn, a catastrophizing partner may be more inhibited during sexual activities and hypervigilant to pain cues from his female partner, interfering with his ability to creatively adapt sexual activities to minimize pain and leading to lower sexual satisfaction for both members of the couple. These findings corroborate a growing number of studies demonstrating that the partners' report of their own behaviors, thoughts, and emotions are directly associated with the psychological and sexual experiences of women with PVD [46,68,69]. The results underscore the importance of including the partner in treatment efforts aimed at improving the sexual satisfaction of affected couples.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In turn, a catastrophizing partner may be more inhibited during sexual activities and hypervigilant to pain cues from his female partner, interfering with his ability to creatively adapt sexual activities to minimize pain and leading to lower sexual satisfaction for both members of the couple. These findings corroborate a growing number of studies demonstrating that the partners' report of their own behaviors, thoughts, and emotions are directly associated with the psychological and sexual experiences of women with PVD [46,68,69]. The results underscore the importance of including the partner in treatment efforts aimed at improving the sexual satisfaction of affected couples.…”
Section: Discussionsupporting
confidence: 85%
“…Despite the distinctly interpersonal nature of PVD because of its relation to sexuality, including both members of the couple in research has only recently gained traction. Further, only a handful of prior studies have examined partner responses to pain in the context of couples' day‐to‐day lives in chronic pain [44,45] and in PVD [46,47]. The novel contribution of the current study was to examine daily associations between male partner responses and sexual and relationship satisfaction in PVD, which represent key aspects of the quality of life of affected couples.…”
Section: Discussionmentioning
confidence: 99%
“…In crosssectional and daily diary studies, greater facilitative partner responses were associated with women's lower intercourse pain [67] and better sexual functioning [68], as well as couples' greater relationship and sexual satisfaction [69,67]. Conversely, greater negative and solicitous partner responses are associated with greater pain [26,67,70,71] and more depressive symptoms in women [72], as well as lower sexual functioning [68] and relationship and sexual satisfaction in couples [69]. Whereas facilitative responses may promote couples' use of adaptive coping strategies and shared emotion regulation in the face of pain, solicitous and negative partner responses may reinforce avoidance of pain and sex and disrupt couples' pain-related coping and emotion regulation.…”
Section: Relationship Factorsmentioning
confidence: 99%
“…) recently completed a two-month daily diary study involving 69 heterosexual couples coping with vulvodynia [43]. They found that a woman's pain during intercourse increased on days when she perceived greater solicitous and negative partner responses, and when her male partner reported greater solicitous and lower facilitative partner responses.…”
Section: Rosen Et Al (In Pressmentioning
confidence: 99%